The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1080/15548732.2014.978930
|View full text |Cite
|
Sign up to set email alerts
|

Functional Adaptation to Foster Care: Foster Care Alumni Speak Out

Abstract: For this qualitative study, 18 foster care alumni, ranging in age from 18 to 25 years, described good foster parents as helping them functionally adapt to foster care. Good foster parents never referred to them as a "foster" child, balanced consistency with individualized application of rules, used terms such as "our family" or "our home," and included them in extended family gatherings and events. They were emotionally available without being intrusive, especially about stressful events in their lives. They f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…Findings in this study were congruent with prior research that suggested these activities are important and can help "normalize" the transition into foster care; at the same time, the attendant expenses are often not covered by board payments and require foster parents to pay out-of-pocket (Affronti, Rittner, & Semanchin Jones, 2015). Future research might explore the potential impact of providing increased financial support to foster parents, specifically to cover these "normalizing" after-school activities.…”
Section: On-going Foster Parent Supportsupporting
confidence: 88%
See 3 more Smart Citations
“…Findings in this study were congruent with prior research that suggested these activities are important and can help "normalize" the transition into foster care; at the same time, the attendant expenses are often not covered by board payments and require foster parents to pay out-of-pocket (Affronti, Rittner, & Semanchin Jones, 2015). Future research might explore the potential impact of providing increased financial support to foster parents, specifically to cover these "normalizing" after-school activities.…”
Section: On-going Foster Parent Supportsupporting
confidence: 88%
“…This study found that children in care experienced ambivalence towards their birth families as well as their foster families that parallels what foster children report as unresolved grief and loss while in placement (Affronti, Rittner, & Semanchin Jones, 2015;Henry, 2005;Samuels, 2009). Study findings with foster care alumni support these foster parents recommendations about the importance of speaking positively about birth parents and developing a collaborative working relationships with birth parents or siblings (Affronti, Rittner, & Semanchin Jones, 2015).…”
Section: Implications For Policy and Practicementioning
confidence: 59%
See 2 more Smart Citations
“…Relational well-being in foster family settings have been operationalized a number of ways, including foster home adjustment (Affronti, Rittner, & Semanchin-Jones, 2015), foster home adaptation (Dunn, Culhane, & Taussig, 2010; Semanchin-Jones, Rittner, & Affronti, 2016), foster home integration (Leathers, 2002; 2006), positive home integration (Authors, 2016a), and child-caregiver therapeutic alliance (Rauktis, De Andrade, Doucette, McDonough, & Reinhart, 2005). These characterizations illuminate the processes occurring within foster family systems that promote successful adjustment and adaptation (Affronti, Rittner, and Semanchin-Jones, 2015; Semanchin-Jones, Rittner, & Affronti, 2016), identify factors which contribute to the development of therapeutic alliance between children and their caregivers (Rauktis, et.…”
Section: Literature Reviewmentioning
confidence: 99%